GEMS-like material in the matrix of the Paris meteorite and the early stages of alteration of CM chondrites. (1st December 2015) - Leroux, H.; Cuvillier, P.; Zanda, B.; Hewins, R.H.
Abstract: The Paris meteorite is a weakly altered CM chondrite that has been discovered recently (Hewins et al., 2014). Its matrix offers the opportunity to search for well-preserved pristine pre-accretional material, as well as to study the earliest stages of aqueous alteration in the CM parent body. The study of the matrix of Paris has been conducted by analytical transmission electron microscopy on focused ion beam sections extracted from matrix areas showing different degrees of aqueous alteration. The least altered matrix sample consists of amorphous silicate grains, a few hundreds of nm in size, separated from one another by an abundant porosity. The amorphous silicates enclose numerous Fe-sulfide nanograins and their average composition is close to the chondritic composition. They share many similarities with GEMS (glass with embedded metal and sulfides) grains present in chondritic-porous interplanetary dust particles and with primitive type 3.0 carbonaceous chondrites. This first discovery of GEMS-like texture in a CM chondrite suggests that GEMS grains could have been the building blocks of the CM matrices. In more aqueously altered samples, pronounced microstructural heterogeneities were detected at the micrometer scale. The matrix consists mostly of a mixture of amorphous material and Fe-rich, spongy to fine-fibrous, poorly crystalline phyllosilicates. The porosity fraction is significantly reduced and the mixed amorphous-fibrous material frequently forms a continuous groundmass. The close association between these two material types suggests a replacement mechanism due to aqueous alteration. Chemical compositions correlate strongly with the microstructure. The amorphous material has a composition close to the chondritic value while the fine-fibrous phyllosilicate material is Fe-enriched. This Fe enrichment is found to be continuous from weakly to more heavily altered areas, in which the fibrous morphology is coarser and better crystalline. Cronstedtite with intercalated tochilinite is also found, but in pore spaces. This chemical evolution, concomitant with the maturation of the phyllosilicates, demonstrates that the early aqueous fluids that interacted with silicates in the matrix were enriched in Fe. This composition is probably the consequence of the preferential dissolution of metal and iron sulfides during the first stages of alteration. The enrichment of phyllosilicates in Mg seen in more altered CM chondrites is not observed in Paris.